Analisis Penerapan Prinsip Objektivitas dalam Evaluasi Hasil Belajar Siswa - Ririn Liliyani Sioh; Santi Aplunggi; Viatni Yakoba Manu (Jurnal Ilmiah Literasi Indonesia, 2026)
Evaluation of learning outcomes is a crucial component of the learning process because it forms the basis for educational decision-making. One of the key principles that must be upheld in evaluation is objectivity, namely, assessment that is free from the influence of assessor subjectivity and based on clear, measurable criteria and standardized instruments. However, in practice, the application of objectivity still faces various challenges, such as teacher personal bias, limited understanding of evaluation techniques, the lack of use of assessment rubrics, and school assessment systems that do not support transparency. This article aims to analyze the application of the principle of objectivity in evaluating student learning outcomes, the factors influencing it, and the challenges faced in assessment practices in schools. This study uses a descriptive qualitative approach through a literature review of various relevant scientific sources. The analysis shows that objectivity can be achieved through the use of valid and reliable instruments, detailed assessment rubrics, assessor consistency, documentation of learning outcomes, and the support of a transparent assessment system in schools. Thus, objective evaluation can produce fair, accurate, and accountable information that reflects students' true abilities.